Impact of Visual Aids in Enhacing the Students Learnig Process at The Univeristy of Narowal - Iqra Khalid; Dr. Rukhsana Sardar; Farah khalid (Journal of Religion and Society, 2026)
This study examines the impact of visual aids on enhancing the students learning process at the University of Narowal. Visual aids help simplify complex concepts, improve information retention, and make classroom instruction more engaging and meaningful. In higher education, visual aids such as charts, graphs, multimedia slides, pictures, whiteboards, and digital tools are increasingly integrated into instructional practices. The objectives of the study were to examine the influence of visual aids on students' learning and engagement, to explore teachers' perceptions regarding their effectiveness, and to identify challenges faced in the use of visual aids. A quantitative research design was employed, and data were collected through a structured questionnaire from 250 participants, including 200-students and 50 teachers, selected through random sampling. Ethical considerations were strictly followed. Data analysis was conducted using SPSS software, applying descriptive statistics and Spearman correlation analysis. The findings revealed that visual aids significantly enhance students' understanding, motivation, concentration, and retention. Teachers also reported improved classroom interaction and lesson organization. Despite challenges such as limited resources and insufficient training, visual aids were found to be essential tools for improving teaching and learning at the university level. Keywords: Visual aids, Learning process